Smart mobility “aquavoyager 8000” / Muhammad Firdaus Mohd Hafzi - Mohd Hafzi, Muhammad Firdaus (Universiti Teknologi MARA, Kedah, 2024)
The AquaVoyager 8000 is a pioneering submersible designed in collaboration with National Geographic for deep-sea biological research in Asia. Engineered to reach depths of up to 8000 meters, this state-of-the-art submersible is equipped with high-definition cameras and sophisticated sampling tools, enabling detailed studies of marine life, geological formations, and ocean currents. Its futuristic design and advanced propulsion system ensure efficient and smooth navigation, while the high-tech interior features intuitive touchscreen pilot systems and joystick controls, providing a user-friendly experience for operators. Safety is a top priority, with redundant systems and a self-righting feature to enhance reliability and security during missions. The AquaVoyager 8000 is tailored to meet the needs of National Geographic's deep-sea biological research team, offering unparalleled capabilities for scientific exploration in challenging underwater environments.